Combining network pharmacology with chromatographic fingerprinting and multicomponent quantitative analysis for the quality evaluation of Astragali Radix. (2nd February 2022) - Li, Xiaohuan; Guo, Xinhua; Sha, Miao; Gao, Wenyuan; Li, Xia
Abstract: Nowadays, cultivated variants and adulterants of Astragali Radix (AR) have flooded the market, causing the quality assurance of AR to be challenging. To address this issue, we combined network pharmacology with chromatographic fingerprinting and multicomponent quantitative analysis for the quality evaluation of AR. Specifically, through network pharmacology, a complete understanding of the active components and pharmacological activities of AR was established. In addition, establishing fingerprint profiles and multicomponent quantitation by high‐performance liquid chromatography (HPLC) is convenient and comprehensive, and can more fully reflect the overall situation of the distribution of various chemical components. To evaluate and differentiate AR from different origins, hierarchical cluster analysis and principal component analysis were performed. The result showed that AR acts synergistically through multiple targets and pathways. The content of chemical components in AR from different origins varied significantly. Combining network pharmacology and multicomponent quantification results, astragaloside II and IV and formononetin can be used as quality markers for the quality control of AR. This study provides a comprehensive and reliable strategy for the quality evaluation of AR and identifies its quality markers to ensure the quality of the herb.